Intimal disruption in type B aortic intramural hematoma. Does size matter? A systematic review and meta-analysis. (15th October 2018) - Moral, Sergio; Ballesteros, Esther; Roque, Marta; Carrato, Cristina; Vilardell, Pau; Brugada, Ramon; Evangelista, Arturo
Abstract: Background: Type B intramural hematoma (IMH) is considered a low-risk entity for aortic complications if aortic dilation, containing rupture or clinical instability are absent. However, the development of intimal disruptions (ID), present in >40% of cases, poses an unknown risk. Objectives: To establish which ID characteristics imply a higher risk of aortic complications and, therefore, merit invasive treatment. Methods: A systematic review and a meta-analysis were made following a search in EMBASE, MEDLINE and PsycINFO for articles published between January 1995 and December 2017. The combined endpoint was defined as aortic mortality, invasive treatment for aortic disease and/or increase in maximum aortic diameter ≥55 mm. Lesions with communicating orifice ≤3 mm were defined as tiny ID (TID) and those with >3 mm as focal ID (FID). Results: Six studies with 564 participants diagnosed of type B IMH were included. Incidence of ID was 54.3% (306 individuals): 27.7% (156 individuals) initially met TID criteria; however, 13.9% of these (21 of 151 with morphologic evolution) evolved to FID within the first 6 months. Ninety-two cases suffered clinical aorta-related events (16.3%; mean follow-up range: 15–85 months; median: 52 months). Patients with TID had a similar risk of aorta-related events to those without ID (RR = 0.904; 95% CI, 0.335–2.440; P = 0.842; I 2 = 42.5%), but lower than those with FID (RR = 0.299; 95% CI, 0.094–0.952; P = 0.041; I 2 = 26.9%). Conclusions: Tiny intimal disruption in type B IMH evolution is not related to an increased risk of complications and should not be considered an indication for invasive treatment. However, since 14% of TID evolve to FID within the first 6 months, close follow-up with imaging techniques is advisable. Highlights: Tiny intimal disruption development in type B IMH should not be considered as an indication of invasive treatment. Tiny intimal disruption presents a better prognosis than focal intimal disruption. Homogenization of ID definitions is mandatory to help clinicians make the correct choice of treatment.